2015
DOI: 10.1002/app.42227
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structure, and properties of segmented carborane‐containing polyurethanes

Abstract: Novel segmented carborane-containing polyurethane (PUR 2-5) is synthesized from hydroxyl-terminated carborane-containing prepolymer (P3) as soft segment and isocyanate-terminated carborane-containing prepolymer (P5) as hard segment by different ratio of P3 and P5. The prepared carborane-containing polyarylesters and polyurethanes (PURs) are characterized by Fourier transform infrared spectroscopy (FTIR) and nuclear magnetic resonance spectroscopy (NMR). Their mechanical properties and thermal stability are mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Polymers with carboranes as building blocks, such as polyurethanes, polythiophenyls, polysiloxanes, and polyimides, are getting some attention due to their good solubility, thermal and thermo‐oxidative stability, and high T g . For example, Huang et al.…”
Section: Methodsmentioning
confidence: 99%
“…Polymers with carboranes as building blocks, such as polyurethanes, polythiophenyls, polysiloxanes, and polyimides, are getting some attention due to their good solubility, thermal and thermo‐oxidative stability, and high T g . For example, Huang et al.…”
Section: Methodsmentioning
confidence: 99%
“…With such an LOI value, the PU-PIL-Gr samples were able to compete with reported PU materials. 38,39 Clearly, the introduction of PIL and Gr into the sponge framework efficiently enhanced the LOI of the resulting modified sponges.…”
Section: Resultsmentioning
confidence: 96%
“…Owing to these distinctive properties, carboranes have been regarded as one of the most excellent organic groups to improve performance of organic polymers with remarkable thermal stability . Therefore, carboranes were incorporated into many traditional polymers to improve their thermal stability including epoxy resins, phenolic resins, polyurethanes, organic silicone polymers, benzoxazine resins, polyimides, and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Carborane groups also can be introduced into polyesters to improve the thermal stability of the polyesters. Decades ago, several research groups have prepared the carborane‐containing polyester with different molecular weight . However, few research works about carborane‐containing polyester have been reported in recent years.…”
Section: Introductionmentioning
confidence: 99%